Exploring Mathematical Literacy in 5th-Grade Elementary Students: A Case Study of Diverse Ability Levels - Ulfiyani,; Wahyudin,; Mardiah, Dede; Mayang Salshabylla, Dewi; Gehan Putri, Yasmin (International Conference on Elementary Education, 2025)
This study aims to understand the mathematical literacy skills of elementary school students. The case study method is involved in this study. The population of 5th-grade students was sampled using purposive with students who have varying mathematical abilities (high, moderate, and low). The instrument relies on a written test containing seven mathematical literacy questions adapted from Wigati's thesis (2020). The analysis highlights the relationship between cumulative mathematical ability scores and mathematical literacy. Students with high scores (SN) exhibit a good understanding of mathematics, while those with low scores (NT) require a greater grasp of fundamental concepts. Another student (AAA) shows higher mathematical literacy scores compared to cumulative mathematical scores, indicating a potentially stronger theoretical understanding than practical application. Individual interviews indicate that the material in the test questions had been previously studied by the research subjects. The participants felt these questions were related to daily life. The three students used different arithmetic operations to solve the questions and had a preference for questions using direct mathematical symbols. This research attempts to identify factors influencing mathematical literacy among 5th-grade students with the hope of contributing to the development of a more adaptive and inclusive mathematics education. However, further research is needed for a broader generalization.